Effects of Broiler Rearing Environment on Transmission of F-Strain Mycoplasma gallisepticum from Commercial Layer Hens to Broiler Chickens: Role of Acid-Base Balance - Olanrewaju, H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2009)
Two trials were conducted concurrently to determine and compare, blood pH, blood gases, hematocrit and hemoglobin in F-strain Mycoplasma gallisepticum (FMG) inoculated layers and FMG contact-infected broilers. At the termination of the study, FMG-inoculated layers had the highest partial pressure of O2 and the lowest partial pressure of CO2 as compared with the other treatment groups. Blood pH values were unaffected by FMG inoculation. Hematocrit and blood concentrations of hemoglobin were slightly higher and HCO3- levels were lowest in FMG contact-infected broilers in comparison to the other treatments groups. Mycoplasma gallisepticum inoculated layers also resulted in a significant increase in blood concentrations of K+, a decrease in Na+, but no significant effects on blood concentrations of Ca2+ and Cl-. There were no differences in plasma glucose, cholesterone, triglyceride and anion gap, but osmolality was significantly reduced in FMG contact-infected broilers. Results indicate that inoculation of layers with FMG vaccine results in changes in plasma acid-base status along with changes in other blood metabolic variables. However, the FMG inoculation did not prevent homeostatic regulation of acid-base balance, as indicated by constant blood pH. The significant increase in pO2 in FMG inoculated layers is generally associated with an oxygen-dependent improvement in tissue oxygenation. Elevated arterial partial pressure of oxygen is beneficial to maximize oxygen transport capacity along with high concentrations of hemoglobin and hematocrit to carry oxygen throughout the body. It was concluded that in addition to protecting birds from MG infection, an FMG vaccine may improve the layer chicken’s ability to withstand the harmful effects of stressors on their performance and well-being.